A study on impact of macroeconomic indicators towards Kuala Lumpur Composite Index (KLCI) - Sulaiman, Mohd Haniff (Faculty of Business and Management, 2014)
This paper is undertaken with the objective to examine the impact of key macroeconomic indicators including interest rates, inflation rates, exchange rates and money supply (M2) towards Kuala Lumpur Composite Index (KLCI) using the multiple linear Regression method. The data gathered from the Data Stream and World Data Bank. Interactive software package E-view would be used for testing and analysing the data collected. Base Lending Rate (BLR) as a measure of interest rates, Consumer Price Index (CPI) as a measure of inflation, exchange rate and money supply (M2) will be use as macroeconomic variables. It is expects that the interest rates, inflation rates, exchange rates and money supply to have a significant impact towards KLCI. However, this paper will only focus on interest rates, inflation rates, exchange rates and money supply to help to understanding regarding the impact of macroeconomic indicators on Kuala Lumpur Composite Index (KLCI). The results of this research paper would provide us with an indicative view and could form an important basis for investors and policy makers in their investment strategies and policy decisions respectively.